Cultura lectora y pensamiento crítico en estudiantes del segundo grado de educación secundaria de la Institución Educativa Nº 60080, Ramón Castilla 2023 - Terrones Oriundo, Kevin David (2025)
Relate reading culture and critical thinking in students of the second grade of secondary education of IE 60080 in the district of Ramón Castilla, in the 2023 school year; was the purpose of the study, for this purpose the quantitative-relational methodology was used and 130 students participated; resulting in the correlation coefficients between the variables showing high and positive correlations between reading culture and critical thinking (0.752), as well as in all the dimensions evaluated: motivation (0.752), concentration (0.730), comprehension (0.702), and reflection (0.705). This implies that as students' reading culture improves, so does their ability to think critically.